Word retrieval ability on semantic fluency task in typically developing Malayalam-speaking children - Sunila John & Bellur Rajashekhar (Child Neuropsychology: A Journal on Normal and Abnormal Development in Childhood and Adolescence, 2014)
Word-retrieval abilities in children can be assessed using word generation or verbal fluency task. The ability to retrieve is related to the individual’s ability to retrieve associated words from the mental lexicon in an organized manner. The present study focuses on the developmental aspects of semantic fluency in 1,015 Malayalam-speaking children in the age range of 5 years to 15 years across both genders. The study revealed a developmental trend in the mean total number of correct word scores, number of clusters generated, and switching scores; however, mean cluster size did not show any statis- tically significant variation. Further, the scores did not vary across genders. Overall, the study indicated a linear developmental trend during verbal fluency with the increase in complexity of strategy use.